PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS V SEKOLAH DASAR - Muhenda Hafidh; Mai Sri Lena (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
This research is motivated by the limited use of attractive and easy-to-understand digital media that can stimulate students in learning. The purpose of this study was to produce learning animated videos using the Canva application for valid and practical integrated thematic learning for class V SD, as well as to determine the validity and practicality of the media being developed. This type of research is development research (R&D). Using a 4D model consisting of several stages (Define, Design, Develop, Dissiminate). This research was only carried out until the development stage (Develop) due to limited time and available funds. The subjects of this study were 3 experts, 1 teacher and 27 students of class V SDN 12 Kampung Durian. The results of research on developing learning media using the Canva application obtained a validity level of 93.75% from the media aspect from the language aspect 95% and from the material aspect 88%. Based on the results of the teacher's response and also the results of the responses of students in research schools in schools it can be seen that learning using learning media the percentage of teacher responses at SDN 12 Kampung durian is 94% while the percentage of student responses is 96.6%. Thus it was concluded that the learning media using the Canva application in integrated thematic learning for class V elementary school had been declared valid and practically used in the learning process. Based on the results of the teacher's response and also the results of the responses of students in research schools in schools it can be seen that learning using learning media the percentage of teacher responses at SDN 12 Kampung durian is 94% while the percentage of student responses is 96.6%. Thus it was concluded that the learning media using the Canva application in integrated thematic learning for class V elementary school had been declared valid and practically used in the learning process. Based on the results of the teacher's response and also the results of the responses of students in research schools in schools it can be seen that learning using learning media the percentage of teacher responses at SDN 12 Kampung durian is 94% while the percentage of student responses is 96.6%. Thus it was concluded that the learning media using the Canva application in integrated thematic learning for class V elementary school had been declared valid and practically used in the learning process